Асоціативно-образні уявлення про козаків і сфера дериваційних процесів української мови - Gutsuliak (München: Verlag readbox unipress / Open Publishing LMU, 2020)
У сучасному українському мовознавстві дослідження образних дериваційно-мотиваційних процесів належить до актуальних, проте мало опрацьованих питань. Формування асоціативно-образних мотиваційних звʼязків є важливим і невідʼємним елементом творення значної кількості похідних лексем української мови з образним змістом. З-поміж них виокремлюємо парадигму образних дериватів, що сформувалася довкола спільної твірної бази – субстантива козак. Вона включає чотири зони похідних утворень: адʼєктивну, субстантивну, дієслівну й адвербіальну. Мета пропонованої розвідки передбачає опис суспільно-історичних та етнокультурних чинників, що зумовили формування низки стереотипних уявлень українців про козаків та відповідно образно-дериваційного потенціалу лексеми козак. In modern Ukrainian linguistics the research of figurative derivative-motivational processes belongs to newsworthy, but little learned. Developing of associative-figurative motivational connections is essential and integral element of forming a significant number of derivative lexemes of Ukrainian language with figurative content. Among them we can distinguish paradigm of figurative derivates, which has been developed around common compound stem – substantive Kozak. It includes four zones of derivative formation: adjective, substantive, verbal, and adverbial. The aim of suggested research anticipates descriptions of socio-historical and ethnocultural factors, which have caused forming of the chain of Ukrainians stereotypical conceptions about Kozaks and relatively figurative-derivational potential of lexemes Kozaks. In modern Ukrainian linguistics the research of figurative derivative-motivational processes belongs to newsworthy, but little learned. Developing of associative-figurative motivational connections is essential and integral element of forming a significant number of derivative lexemes of Ukrainian language with figurative content. Among them we can distinguish paradigm of figurative derivates, which has been developed around common compound stem – substantive Kozak. It includes four zones of derivative formation: adjective, substantive, verbal, and adverbial. The aim of suggested research anticipates descriptions of socio-historical and ethnocultural factors, which have caused forming of the chain of Ukrainians stereotypical conceptions about Kozaks and relatively figurative-derivational potential of lexemes Kozaks.
Keywords: Ключові слова: відсубстантивні деривати, козак, образна мотивація, образна парадигма, образно-дериваційний потенціал слова, стереотипні уявлення. Keywords: substantivized derivates, Kozak, figurative motivation, figurative paradigm, figurative-derivational potential of a word, stereotypical conception.